Aspects of the Iron Age coinages of northern East Anglia with especial reference to hoards - Chadburn, Amanda Dorothy Barras (2006)
This thesis considers the Iron Age coinages found in hoards within a particular study area in northern East Anglia. The study area was widely defined to attempt to capture all the coins considered by previous scholars to belong to the Iron Age tribe, the Iceni. Other coins of the Iceni outside the study area found in hoards are also considered.